STUDENTS TRAINING TO CONDUCT ENVIRONMENTAL AUDITS (THROUGH THE EXAMPLE OF THE RUSSIAN STUDENT ENVIRONMENTAL SEMINAR) - M. N. Strukova; E. V. Patrakov; L. V. Strukova (Russian State Vocational Pedagogical University, 2017)
The aim of the work described in the article is the search for new intensive methods of training providing formation of students-ecologists readiness to conduct environmental audits and to ensure the safe living environment.Methodology and research methods. The practice-focused and competencebased approaches to training of future environmental engineers became a basis of the method of training offered by the authors. Diagnostics of formation of readiness among students for implementation of professional activity was carried out with the use of a complex of psychological and pedagogical indicators which were established during questioning, poll and testing. The data were processed by the methods of descriptive statistics and correlation analysis with application of a package of the statistical programs SPSS 17.Results. The experience of the Ural Federal University teachers on the implementation of the innovative project «Russian Student Socio-Environmental Seminar (RSES)» is presented. A set of psychological and pedagogical conditions for the formation of readiness to conduct environmental audits for future engineers and environmentalists based on developed in university concepts of environmental education, safe living and learning in the multiprofessional team experts are presented. The program includes a combination of practical exercises, studies in game form - an intensive educational program; students' valuable attitude towards ecological safety raises, knowledge of technological methods of audit is acquired, communicative skills are improved. The role of practice in professional formation of future environmental engineers is disclosed; set of psychological and pedagogical conditions of transition from mainly information training to the training stimulating independence of the made decisions for transformation of sociocultural and professional experience to personal qualities is described.Scientific novelty consists in the further development of multiprofessional approach concept in terms of interactive educational programs. In this paper the authors prove a high psycho-pedagogical effectiveness of the approach: due to training in polyprofessional team students have an opportunity to seize a large amount of competences in shorter terms.Practical significance. The article can be interesting for organizers of environmental seminars and trainings, various ecological workshops, as well as trainers in the field of life safety.